Problems of Translating Culture-Specific Terms, Realies Which Existed In the Uzbek Language - et. al., Niyozova Shoira Tairovna, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The article covers a broad range of culture-bound words, realia translation, the identification of the main types and difficulties of translation based on the material of literary works translated from Uzbek into English. There was analyzed the presentation of national and historical realias and national features, problems of similarity and equivalency in translated artistic composition.